PENGARUH MODEL PEMBELAJARAN BERBASIS PROYEK DENGAN MENGGUNAKAN VIDEO UNTUK MENINGKATKAN PEMAHAMAN MATERI PEMBELAJARAN EKONOMI - Mistariani Lase; Eka Septianti Laoli; Asali Lase; Arianto Lahagu (Direktorat Riset dan Pengabdian pada Masyarakat (DRPM) Universitas Bina Darma, 2025)
One of the causes of the decline in student learning outcomes is due to the learning method that is still conventional. The purpose of this study is to determine the effect of project-based learning models using videos on students' understanding of economic learning materials at SMP Negeri 2 Gunungsitoli Utara. The research method used is a quantitative research method. The results of the study show that based on the results of the hypothesis test, the t-count value is obtained = 5.413, then the t-count value is confirmed on the t-table value from the critical value for the t-distribution with a significant level of 5% (α = 0.05) with dk = 45. While the critical value of the t-distribution is obtained t-table value of 1.680. So because the t-count value = 5.413 is greater than the t-table value = 1.680, then accept Ha and reject H0 which means there is an effect of project-based learning models using videos on the understanding of Economic learning materials for grade VII students at SMP Negeri 2 Gunungsitoli Utara.